History of the Development of Nagham Al-Qur'an in Indonesia - Suarni, Suarni; Syukrinur, Syukrinur (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2023)
Nagham is an art form of reciting the Quran. The application of art in reciting the Quran is highly dependent on the rules of Tajweed. Reciting the Quran according to Tajweed rules is a command found in the Quran and Hadith. By reciting the Quran by the rules of recitation, a beautiful sound melody called "nagham" is created. However, this artistic melody does not have a musical scale or musical notes. Therefore, the focus of this research is to examine the development of nagham in Indonesia. This study aims to explore the development of Nagham in Indonesia in greater detail. The method used is descriptive and analytical. This research reveals that there are seven nagham styles in Indonesia: Bayyati, Shaba, Hijas, Nahawan, Rast, Sika, and Jiharkah. On the other hand, the application of nagham varies among different reciters (qari).